Evaluation of explosion loading effects on concrete infrastructures using ABAQUS software - Rahimi, Abolfazl (International Journal of Engineering and Technology, 2015)
One of the most important facilities of a country is Fluid Reservoirs which should be secured against different damage of explosion.Â  Reservoir structural failure after explosion not only could lead to economic losses, but also could cause water shortage and toxic leakage. In this paper a reservoir is modeled in ABAQUS software. The results for displacements and deformations, energy dissipation of various forms and principal stresses are illustrated.